2016
DOI: 10.23907/2016.049
|View full text |Cite
|
Sign up to set email alerts
|

The Laryngohyoid Complex in Medicolegal Death Investigations

Abstract: The laryngohyoid complex, composed of the hyoid bone and laryngeal cartilages, can be of interest in the autopsy setting, particularly when injuries are observed. Analysis of trauma to this structure can assist in establishing cause and manner of death. In many situations, the forensic anthropologist, with their expertise in analyzing bone and cartilage trauma, can assist in analyzing trauma to this complex. Although researchers have tried to study the relationships between causes of trauma to the osseocartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Therefore, when conducting an autopsy of a person died due to fatal pressure on the neck as in hanging, manual strangulation or when other pathological conditions are expected in and around the neck such as carcinomas or perforating injuries (including firearm injuries) an understanding of the standard anatomy of this region as well as the possible variations (as mentioned above) would prove to be of immense assistance for accurate interpretation of gross anatomical and radiological findings. (6) In a retrospective study done in Netherland using 284 postmortem examination findings of deaths due to different forms of pressure on the neck, it was found that only 20% had fractures of the hyoid bone and fractures of the thyroid cartilage were twice as common as in the hyoid, amounting to 40%. (18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when conducting an autopsy of a person died due to fatal pressure on the neck as in hanging, manual strangulation or when other pathological conditions are expected in and around the neck such as carcinomas or perforating injuries (including firearm injuries) an understanding of the standard anatomy of this region as well as the possible variations (as mentioned above) would prove to be of immense assistance for accurate interpretation of gross anatomical and radiological findings. (6) In a retrospective study done in Netherland using 284 postmortem examination findings of deaths due to different forms of pressure on the neck, it was found that only 20% had fractures of the hyoid bone and fractures of the thyroid cartilage were twice as common as in the hyoid, amounting to 40%. (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Minor variations in hyoid-larynx comples consist of age-related fusion of the body with the greater and/or lesser horns by ankyloses of the joints etc. (6) (7) Several anomalies and anatomical variations are in record with relation to the thyroid cartilage as well. Thyroid cartilage calcification, cystic changes in the thyroid cartilage, agenesis of the thyroid cornuae, presence of triticeaous cartilages, ectopic superior thyroid cornuae, terminal segmentation of the thyroid cornuae and buckled thyroid cartilage are some of them.…”
Section: Figure 2: Human Hyoid Bonementioning
confidence: 99%
“…Rare calcification of cricoid cartilage has been detected as young as seven years [ 36 ]. For more details on the development and anatomical structure of these tissues, consult Ubelaker [ 1 ] and Pinto [ 2 ].…”
Section: The Structuresmentioning
confidence: 99%
“…Since the 1992 review, a vast literature has emerged on the impact of throat trauma on structures of the throat [ 2 , 3 ]. This article reviews key aspects of that literature presenting the diverse types of neck trauma that can fracture the hyoid, thyroid, and cricoid and impact related tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The laryngohyoid complex and cervical vertebrae have predictable mechanistic fractures based on the application and direction of blunt load, which are easily identifiable [8,23]. Fractures of the hyoid bone may occur in one or more of its five segments as a result of BFT [14], however fractures specifically resulting from compressive injury (i.e., hanging) have typically been recorded in the greater horns [7,17,24]. For the thyroid cartilage, Khokhlov [7] described fractures of the upper horns as the most common in neck compression injuries and were usually transverse and oblique in form.…”
Section: Introductionmentioning
confidence: 99%